2015
DOI: 10.1007/s10973-015-4650-9
|View full text |Cite
|
Sign up to set email alerts
|

Combining Flash DSC, DSC and broadband dielectric spectroscopy to determine fragility

Abstract: New experimental results focused on Flash DSC, DSC and broadband dielectric spectroscopy investigations are reported in this work. The fictive temperatures and fragility indexes are estimated from Flash DSC experiments and compared to values obtained from classical DSC. The consistency of the Tool-NarayanaswamyMoynihan model and fragility concept is then investigated over a large range of cooling rates. Indeed, the Flash DSC allows exploring thermal properties of materials over a continuous and broad range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…One of the most recent tools developed by Mettler Toledo is the Flash DSC (Fast Scanning Calorimetry or FSC hereafter) device based on a calorimeter chip (Mathot et al, 2011;van Herwaarden et al, 2011;Schick, 2010a, 2010b) which can accurately provide very high cooling rates (up to 4000 °C/s) in a wide range of temperature and therefore could permit to avoid recrystallization of most highly crystallogenic systems. Furthermore, this technique has largely proven its worth in the investigation of disordered polymeric and metallic systems (Cangialosi et al, 2016;Dhotel et al, 2015;Gao et al, 2016;Monnier et al, 2017bMonnier et al, , 2017aMonnier et al, , 2017cSchick and Androsch, 2016;Simon and Koh, 2016). Therefore, up to our knowledge, few studies are reported in the case of small organic molecular compounds (Corvis et al, 2015a(Corvis et al, , 2015bKawakami et al, 2012;Magoń et al, 2015;Schammé et al, 2017;Shamim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most recent tools developed by Mettler Toledo is the Flash DSC (Fast Scanning Calorimetry or FSC hereafter) device based on a calorimeter chip (Mathot et al, 2011;van Herwaarden et al, 2011;Schick, 2010a, 2010b) which can accurately provide very high cooling rates (up to 4000 °C/s) in a wide range of temperature and therefore could permit to avoid recrystallization of most highly crystallogenic systems. Furthermore, this technique has largely proven its worth in the investigation of disordered polymeric and metallic systems (Cangialosi et al, 2016;Dhotel et al, 2015;Gao et al, 2016;Monnier et al, 2017bMonnier et al, , 2017aMonnier et al, , 2017cSchick and Androsch, 2016;Simon and Koh, 2016). Therefore, up to our knowledge, few studies are reported in the case of small organic molecular compounds (Corvis et al, 2015a(Corvis et al, , 2015bKawakami et al, 2012;Magoń et al, 2015;Schammé et al, 2017;Shamim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Quenching was performed in situ on the chip sensor, and then the sample was heated at the same rate for comparison. The mass of the samples was estimated by comparing the values of ΔC p (T g ) obtained by Flash DSC and conventional MT-DSC on quenched PHBV, following a procedure already reported elsewhere 51,66. The heat flow signals were normalized to the sample mass(11,44, and 36 ng, respectively) and evenly shifted for the sake of clarity.…”
mentioning
confidence: 99%
“…36 Particularly, this technique is frequently used to investigate relaxation processes in glassforming materials, 37,38 polymers, [39][40][41][42][43][44][45] and is also increasingly employed when studying structural connement. [46][47][48][49][50][51][52] It can also be valuable when studying structural transitions within highlyordered liquid and plastic crystals.…”
Section: Resultsmentioning
confidence: 99%